2009
DOI: 10.1515/znb-2009-0810
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-(2-Aminophenyl)-4-arylquinazoline Derivatives by Reaction of 2-Aminoarylbenzimidamides with Isatoic Anhydride

Abstract: A series of 2-(2-aminophenyl)-4-arylquinazoline derivatives (5a -j), with various 4-substituents, have been synthesized by one-pot cyclization in 66 -79 % yield by heating 2-aminoarylbenzimidamides 3a -j with isatoic anhydride (4). The high yield and simplified workup procedure, in addition to the neutral reaction conditions, are the main advantages of our approach. The structure of the product 5e was further confirmed by single-crystal X-ray structure analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…By a similar technique, El-Shaieb in 2009 with co-authors [42] presented a method for the synthesis of aminoquinazolines 59 by aminoarylbenzamidine reaction 1'' and 4formyl The same group of scientists in 2009 [43] investigated the reaction of 2-aminoarylbenzimidamides 1'' with isatoic anhydride 60. It was found that as a result of boiling these substrates in absolute ethanol for 2-3 hours, 2-(2-aminophenyl)-4-arylquinazoline derivatives 61 are formed with a yield of 67-79 % (Scheme 46).…”
Section: Preparation Of 4-phenylaminoquinazolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…By a similar technique, El-Shaieb in 2009 with co-authors [42] presented a method for the synthesis of aminoquinazolines 59 by aminoarylbenzamidine reaction 1'' and 4formyl The same group of scientists in 2009 [43] investigated the reaction of 2-aminoarylbenzimidamides 1'' with isatoic anhydride 60. It was found that as a result of boiling these substrates in absolute ethanol for 2-3 hours, 2-(2-aminophenyl)-4-arylquinazoline derivatives 61 are formed with a yield of 67-79 % (Scheme 46).…”
Section: Preparation Of 4-phenylaminoquinazolinesmentioning
confidence: 99%
“…The same group of scientists in 2009 [43] investigated the reaction of 2‐aminoarylbenzimidamides 1′′ with isatoic anhydride 60 . It was found that as a result of boiling these substrates in absolute ethanol for 2–3 hours, 2‐(2‐aminophenyl)‐4‐arylquinazoline derivatives 61 are formed with a yield of 67–79 % (Scheme 46).…”
Section: Aminoquinazolines and Their Derivativesmentioning
confidence: 99%